Pd nanocrystals anchored on 3D hybrid architectures constructed from nitrogen-doped graphene and low-defect carbon nanotube as high-performance multifunctional electrocatalysts for formic acid and methanol oxidation. (June 2020) - Ren, J.; Zhang, J.; Yang, C.; Yang, Y.; Zhang, Y.; Yang, F.; Ma, R.; Yang, L.; He, H.; Huang, H.
Abstract: Palladium (Pd)-based catalysts have captured considerable attention owing to their abundant reserve and strong resistance to CO species in both direct formic acid fuel cell and direct methanol fuel cell. As is well known, immobilizing Pd nanocrystals onto conductive graphene support is a reasonable strategy to promote the metal catalytic efficiency. Nevertheless, Pd nanocrystals dispersed onto graphene substrate prepared from insulative graphene oxide sheets easily suffer from high charge-transfer resistance as well as serious agglomeration, which largely deteriorate their electrocatalytic performance. Herein, we report the design and fabrication of Pd nanocrystal-decorated three-dimensional (3D) hybrid architectures constructed from nitrogen-doped graphene and low-defect carbon nanotube (Pd/NG-LCNT) through a facile and cost-effective bottom-up method. Owing to the large specific surface area, 3D interconnected porous configuration, optimized electronic structure, and low carbon defect density, the resulting Pd/NG-LCNT architecture is endowed with unusual catalytic abilities toward both formic acid and methanol electrooxidation, including large electrochemically active surface area value, high mass/specific activity, and reliable lifespan, far surpassing those of conventional Pd/carbon black, Pd/acid-treated carbon nanotube, and Pd/graphene catalyst. Graphical abstract: An efficient bottom-up approach is developed to the construction of Pd nanocrystal-decorated 3D hybrid architectures built from nitrogen-doped graphene and low-defect carbon nanotube. Benefiting from the 3D porous structure as well as low defective nature, the as-derived hybrid catalyst possesses multifunctional electrocatalytic abilities for both formic acid and methanol oxidation reactions. Image 1 Highlights: The growth of ultrafine Pd on 3D N-codoped graphene/low-defect CNT networks is achieved. The porous carbon frameworks largely shorten the diffusion length for electrolytes. The presence of low-defect CNTs ensures a high electron conductivity. The obtained catalyst possesses multifunctional catalytic ability for DFAFC and DMFC.